Challenges in vascular tissue engineering for diabetic patients. (1st April 2018) - Dhulekar, Jhilmil; Simionescu, Agneta
Graphical abstract: Abstract: Hyperglycemia and dyslipidemia coexist in diabetes and result in inflammation, degeneration, and impaired tissue remodeling, processes which are not conducive to the desired integration of tissue engineered products into the surrounding tissues. There are several challenges for vascular tissue engineering such as non-thrombogenicity, adequate burst pressure and compliance, suturability, appropriate remodeling responses, and vasoactivity, but, under diabetic conditions, an additional challenge needs to be considered: the aggressive oxidative environment generated by the high glucose and lipid concentrations that lead to the formation of advanced glycation end products (AGEs) in the vascular wall. Extracellular matrix-based scaffolds have adequate physical properties and are biocompatible, however, these scaffolds are altered in diabetes by the formation AGEs and impaired collagen degradation, consequently increasing vascular wall stiffness. In addition, vascular cells detect and respond to altered stimuli from the matrix by pathological remodeling of the vascular wall. Due to the immunomodulatory effects of mesenchymal stem cells (MSCs), they are frequently used in tissue engineering in order to protect the scaffolds from inflammation. MSCs together with antioxidant treatments of the scaffolds are expected to protect the vascular grafts from diabetes-induced alterations. In conclusion, as one of the most daunting environments that could damage the ECM and its interaction with cells is progressively built in diabetes, we recommend that cells and scaffolds used in vascular tissue engineering for diabetic patients are tested in diabetic animal models, in order to obtain valuable results regarding their resistance to diabetic adversities. Statement of Significance: Almost 25 million Americans have diabetes, characterized by high levels of blood sugar that binds to tissues and disturbs the function of cardiovascular structures. Therefore, patients with diabetes have a high risk of cardiovascular diseases. Surgery is required to replace diseased arteries with implants, but these fail after 5–10 years because they are made of non-living materials, not resistant to diabetes. New tissue engineering materials are developed, based on the patients' own stem cells, isolated from fat, and added to extracellular matrix-based scaffolds. Our main concern is that diabetes could damage the tissue-like implants. Thus we review studies related to the effect of diabetes on tissue components and recommend antioxidant treatments to increase the resistance of implants to diabetes.